DOMESTIC ABUSE AND TRANSFORMATION IN ALICE WALKER’S NOVEL "THE COLOR PURPLE” - Hassooni Abdullah, Lecturer Rasha (Opción)
Alice Walker African American womanist who won the Pulitzer Prize awarded for her fiction in 1983 for epistolary novel The Color Purple (1982), she gives her voice to those who had no voice. The color purple is a masterpiece of Alice walker focuses on the struggle and discriminations of African American women on the hand of black and white men together .On the other hand, the novel shed the light on Celie, protagonist of the novel lost her mom and her innocence to the man she call him Pa. She raped many times and conceived two children; hyper efficient house women who is highly abused in a very violent domestic disturbance environment. The impact of her beloved sister Netti, she was Celie refuge as the novel goes as series of letters. Methods: The researchers focus on the role of the family, society and how the male characters oppress and discriminate the women through the novel. Results: However the researchers conclude how those women stand against the difficulties and found their identity through unity and women- bonding and women should join together and support each other to reject male dominance and self-recognition. Conclusion: Thus, Shug tries and support Celie to identify herself as a creature, as a human being and as a black woman.